ANALISIS PENGARUH INFLASI, FOREIGN DIRECT INVESTMENT DAN INTEREST RATE TERHADAP HARGA SAHAM SEKTOR PROPERTI - Robith, Zaidar; Wahyudi, Setyo Tri (Islamic Economics and finance in Focus, 2022)
This study aims to determine the effect of inflation factors, foreign direct investment and interest rates on stock prices in the property sector listed on JII70. This study uses secondary data, namely primary data obtained from the Indonesia Stock Exchange (IDX), Bank Indonesia (BI), the World Bank and the Central Statistics Agency (BPS). This study uses a quantitative approach with descriptive statistical analysis techniques and uses the Vector Autoregressive (VAR) / Vector Error Correction Model (VECM) test. VAR is used when the data used is stationary at the level level. However, if the data is not stationary at the level, the next analysis will be compared using the VECM method. This study uses a purposive sampling method, namely the selection method with certain criteria. The results of this study indicate that inflation, which is represented by the CPI value, has a positive influence on changes in sharia share prices in the property sector in Indonesia in the long and short term. Foreign direct investment, which is represented by the value of net foreign direct investment, has a positive influence on changes in sharia share prices in the property sector in Indonesia in the short term. In the long term, foreign direct investment has insignificant returns, although it has a positive effect as well. Meanwhile, the interest rate represented by the BI Rate has a negative effect on changes in sharia share prices in the property sector in Indonesia in the long term, but on the contrary has a positive effect in the short term.